2003
DOI: 10.1002/elps.200390122
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring liposome‐mediated delivery and fate of an antisense drug in cell extracts and in single cells by capillary electrophoresis with laser‐induced fluorescence

Abstract: Capillary electrophoresis with laser-induced fluorescence (CE-LIF) detection was used for evaluation of the effectiveness of delivery and fate of a model 25-mer DNA-based phosphorothiate antisense drug in cells. The antisense molecule was delivered to the cells through a simple incubation and by using a cationic liposome (Cytofectin GS 3815). The cationic lipid interacted with the negatively charged antisense to form a more positively charged complex. It was observed that uptake of the liposome-antisense compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…CE has proved to be an efficient tool for studying molecular interactions [9][10][11][12][13][14][15][16][17] encompassing determination of stability constants, complexation stoichiometry and distribution, and partitioning coefficients. Also, CE has been used to assess liposomal drug delivery systems in a few cases [18][19][20][21][22]. Liposomes have, however, primarily been introduced into capillaries in studies directed at estimating drug lipophilicity in relation to membrane permeability properties [2][3][4][5][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…CE has proved to be an efficient tool for studying molecular interactions [9][10][11][12][13][14][15][16][17] encompassing determination of stability constants, complexation stoichiometry and distribution, and partitioning coefficients. Also, CE has been used to assess liposomal drug delivery systems in a few cases [18][19][20][21][22]. Liposomes have, however, primarily been introduced into capillaries in studies directed at estimating drug lipophilicity in relation to membrane permeability properties [2][3][4][5][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…The various mutation analyses that are referred to in this article showed that the use of -CE-LIF detection could make the process easier and faster than traditional methods [86][87][88][89][90][91]. CE was also used for antisense drug analysis, viral DNA detection, mRNA analysis, and gene expression [92][93][94][95][96][97]. Considering the importance of the CE work in this field, only recent studies are listed here.…”
Section: Ce In Transcriptomicsmentioning
confidence: 99%
“…Due to the biological properties of liposomes, these structures are currently under extensive study as nanocarriers for targeted drug delivery . It should come as no surprise that CE is used in this research to verify the encapsulation and selective release of the cargo carried in these nanovehicles . An important aspect of many preparations in biological processes is the presence of a pH gradient across the membrane.…”
Section: Ce Separations Of Nanomaterialsmentioning
confidence: 99%